The Jewish community in New Zealand : a contribution to the study of assimilation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - Collins, Patricia R (Massey University, 1971)
Numerous references have been made to the dearth of material on New Zealand's immigrant minority groups. 1 For example: Thompson, R., 1963, 16. Harper, A.G. in an introduction to Lochore, R.A., 1951, 5. Although listing a bibliography of approximately 90 references on immigrants and immigration in New Zealand, Thomson and Trlin in their recently published Immigrants in New Zealand ventured the opinion that, "there are still serious gaps in our knowledge and that there is a definite need for further research on all aspects of immigration, immigrants, ethnic group adjustments, assimilation and so on".2 Trlin, A.D. in Thomson, K.W. and Trlin, A.D. (ed.), 1970, 196. With the exception of L.M. Goldman's The History of the Jews in New Zealand and R.A. Lochore's From Europe to New Zealand (which contains a section on the Jewish people) no specialist work has been completed on the Jewish people of New Zealand. This thesis aims therefore to make a detailed study of the New Zealand Jewish community in its New Zealand environment for two purposes: a) as a contribution to the literature on the New Zealand Jewish community, and b) on a broader base, a contribution to the greater understanding of immigration, settlement end assimilation of racial and ethnic minority groups in New Zealand. More specifically it is aimed to: i) examine the origins, growth and development of Jewish settlement in New Zealand ii) to describe similarities to, and differences from, New Zealand's spatial, demographic, social and economic norms in the Urban Areas of Auckland, Wellington and Christchurch where 79 percent of the Jewish population reside. In other words, to examine the pattern of assimilation of Jewish people into New Zealand life and comment on one of the central problems of contemporary Jewish life in New Zealand - the question of survival.
Keywords: New Zealand Jews; Assimilation (Sociology)